Analisis Preventive Maintenance Mesin Compressor dengan Mean Time Beetween Failure dan Mean Time to Repair di PT Suzuki Indomobil Motor - Yayan Heru Haerudin; Wisnu Dwi Wibowo (LPPM Sekolah Tinggi Teknologi Nusantara Lampung, 2024)
The manufacturing industry is experiencing rapid growth in technology and machine maintenance methods to improve operational efficiency and corporate competitiveness. PT Suzuki Indomobil Motor, as a motor vehicle manufacturer, utilizes various machines and equipment in its production processes, one of which is the compressor that serves as the primary air supply source. Failures or malfunctions in the compressor can lead to increased operational costs and significant production downtime. Therefore, an optimal preventive maintenance strategy is required. This study aims to analyze the effectiveness of preventive maintenance using the Mean Time Between Failure (MTBF) and Mean Time to Repair (MTTR) methods to enhance machine reliability and production efficiency. The results indicate that the compressor's availability value is above 95%, signifying that the machines are in good condition. With a more optimized preventive maintenance plan, companies can reduce repair costs, minimize downtime, and enhance machine reliability in the long term.